Determining Food Insecurity: An Application of the Rasch Model with Household Survey Data in Uganda - Owino, Abraham; Wesonga, Ronald; Nabugoomu, Fabian (International journal of food science, 2014)
The inexplicable nature of food insecurity in parts of Uganda and worldwide necessitated an investigation into the nature, extent, and differentials of household food security.Themain objective of this study was to examine the food security dynamics and model household food insecurity.The Raschmodelling approach was employed on a dataset froma sample of 1175 (Tororo = 577; Busia = 598) randomly selected households in the year 2010. All households provided responses to the food security questions and none was omitted from the analysis. At 5 percent level of significance the analysis indicated that Tororo district average food security assessment (0.137 ± 0.181) was lower than that for Busia district (0.768 ± 0.177). All the mean square fit statistics were in the range of 0.5 to 1.5, and none of them showed any signs of distortion, degradation, or less productivity formeasurement.This confirmed that items used in this study were very productive for measurement of food security in the study area.The study recommends further analysis where item responses are ordered polytomous rather than the dichotomous item response functions used. Furthermore, consideration should be given to fit models that allow for different latent distributions for households with children and those without children and possibly other subgroups of respondents.
Keywords: Food Insecurity; Household Survey; Uganda